Fabrication of hydrogel-bioactive glass composite scaffolds for bone tissue engineering - Barros, Manuel João Salazar Guedes de (2016)
Bone is an extremely important connective tissue in the human body, as it provides support and protection of internal organs, being also metabolically relevant as the main mineral reservoir and assuring haematopoiesis through the bone marrow. Due to the current ageing of the population, an increase in bone tissue related diseases is noticeable. Thus, more efficient therapies for treating bone diseases is crucial. Tissue Engineering appears as a promising technology for treating several of those problems, such as bone loss and joint problems. In the present work, composite biomaterials composed of a polymeric hydrogel matrix reinforced with bioactive glass particles were prepared. Individually, these materials have a high water content, which enhances their diffusive transport properties, and display osteogenic properties, respectively. The selected polymer was RGD functionalized pectin, due to its interesting properties, such as biocompatibility, cell-adhesive characteristics and adequacy for cell entrapment, and the bioactive glass selected was a novel alkali-free formulation of 70% diopside and 30% tricalcium phosphate (Di-70), composed of SiO2, CaO, MgO and P2O5. Several different composite formulations were tested, in which pectin concentration, bioactive glass content and glass particle size were varied. The biocomposite’s viscoelastic properties were assessed, as well as their biological behaviour through cytotoxicity assays, and osteogenic character by incubating mesenchymal stem cell (MSC)-laden composites into both basal and osteogenic media for up to 21 days. The results obtained demonstrated that a composite biomaterial with tuneable mechanical properties was successfully prepared, with in situ crosslinking ability within therapeutically relevant timeframes, and not requiring additional crosslinking strategies besides its own composition. Furthermore, its intrinsic osteogenic properties due to the glass composition provided the adequate conditions for promoting the differentiation of MSCs without osteogenic stimulation. The combined properties achieved indicate that the biocomposites prepared are suitable candidate cellularized biomaterials for bone tissue engineering applications.